2005
DOI: 10.1002/eji.200535110
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative difference between the cytotoxic T lymphocyte responses to melanocyte antigens in melanoma and vitiligo

Abstract: Vitiligo is a skin disorder characterized by depigmented macules secondary to melanocyte loss. An unusual facet is its relation to melanoma: Cytotoxic T lymphocytes directed to melanocyte antigens are found in both conditions and imply a breakdown of tolerance, yet the resulting immune reaction is the opposite. The mechanisms at the basis of these opposite effects are not known. Here, we performed a direct comparison of whole melanocyte-specific T cell populations in the two diseases. We demonstrate that neith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 38 publications
1
26
0
1
Order By: Relevance
“…However, only vitiligo cells showed T-cell-receptor down-regulation and IFN-γ production after exposure to HLA-matched melanoma cells, suggesting a qualitative difference in receptor affinity in the two groups. Vitiligo has been considered the effective variant of melanoma immunity [216,217]. Van den Boorn et al [218] expanded on all these findings in 2009: their study showed a prominent role for T-cells in vitiligo pathogenesis, being causative rather than just a consequence of other stimuli.…”
Section: Antigen-specific T-cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, only vitiligo cells showed T-cell-receptor down-regulation and IFN-γ production after exposure to HLA-matched melanoma cells, suggesting a qualitative difference in receptor affinity in the two groups. Vitiligo has been considered the effective variant of melanoma immunity [216,217]. Van den Boorn et al [218] expanded on all these findings in 2009: their study showed a prominent role for T-cells in vitiligo pathogenesis, being causative rather than just a consequence of other stimuli.…”
Section: Antigen-specific T-cellsmentioning
confidence: 97%
“…One patient showed Melan-A and tyrosinase specificity after in vitro re-stimulation [215]. Palermo et al [216] utilized the tetramer technique with peripheral blood of patients with vitiligo or melanoma and showed the presence of Melan-A-specific cytotoxic T-cells at similar levels in both HLA-A2-matched groups. However, only vitiligo cells showed T-cell-receptor down-regulation and IFN-γ production after exposure to HLA-matched melanoma cells, suggesting a qualitative difference in receptor affinity in the two groups.…”
Section: Antigen-specific T-cellsmentioning
confidence: 98%
“…In most cases, central tolerance operates to limit the immune response by negatively selecting highly responsive T cells during development in the thymus. Responsive cells to selfantigens that do survive and leave the thymus to populate the periphery are generally cells that are of lower affinity for selfpeptides and as such are much more difficult to stimulate [57,58]. Furthermore, peripheral tolerance in the form of T regs (CD4 + CD25 + ) and/or T-cell anergy prevent selfresponsive T cells from targeting random cells and in essence triggering an auto-immune response [59].…”
Section: Recombinant Listeria Vaccines Are Capable Of Impacting On Thmentioning
confidence: 97%
“…However, melanoma-infiltrating T cells display a profound reduction in the affinity for their antigens. Additionally, T cells from vitiligo patients were capable of efficient IFN-γ production and TCR downregulation in response to HLA-matched melanoma cells, whereas melanoma-derived T cells were not [86]. These findings suggest that in melanoma the slow rise in peripheral antigen presentation of melanocyte antigens, resulting from progressive tumor necrosis, most likely tunes responsive T cells.…”
Section: Implications For Autoimmunity and Immunotherapymentioning
confidence: 91%